2016
DOI: 10.1080/14686996.2016.1240006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of poly(ethylene glycol)-conjugated phospholipids with supported lipid membranes and their influence on protein adsorption

Abstract: We studied real-time interaction between poly(ethylene glycol)-conjugated phospholipids (PEG-lipids) and a supported lipid membrane by surface plasmon resonance (SPR) spectroscopy to understand dynamic behaviors of PEG-lipids on living cell membranes. Supported lipid membranes formed on a hydrophobic surface were employed as a model of living cell membrane. We prepared three kinds of PEG-lipids that carried alkyl chains of different lengths for SPR measurements and also performed fluorescence recovery after ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…About the complex surface, of which the zeta potential varied from negative to positive, followed AuNR functionalization, and then changed to negative after FA functionalization. Negatively charged nanocarriers have been demonstrated to have better tumor penetration . We diluted FA to different concentrations to obtain its standard concentration curve by UV–vis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About the complex surface, of which the zeta potential varied from negative to positive, followed AuNR functionalization, and then changed to negative after FA functionalization. Negatively charged nanocarriers have been demonstrated to have better tumor penetration . We diluted FA to different concentrations to obtain its standard concentration curve by UV–vis.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we designed the first strategy based on combining AuNRs with exosomes for tumor‐targeted chemo‐photothermal therapy. Previous studies have reported that the amphiphilic molecule 1,2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine‐poly(ethylene glycol) (DSPE‐PEG) could assemble itself into the phospholipid layer of cells . In this strategy ( Scheme ), we generated exosomes by culturing donor cells in medium containing arginyl–glycyl–aspartic acid (RGD)‐functionalized DSPE‐PEG (DSPE‐PEG‐RGD) and sulfhydryl‐functionalized DSPE‐PEG (DSPE‐PEG‐SH) as our previous studies .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy is the hydrophobic insertion used to functionalize the EVs' membranes by exploiting the phospholipid composition of plasma membranes. Amphiphilic molecule DSPE-PEG, FDA approved for medical applications, can self-assemble in the phospholipid bilayer [144]. Based on this consideration, if DSPE-PEG is bound to the molecule of interest, it can be incorporated inside the cell membrane, making it overexpresses the molecule on its surface and producing EVs with the desired functionalization.…”
Section: Indirect Surface Functionalizationmentioning
confidence: 99%
“…However, direct covalent modification of the proteins at the cell cytoskeleton can substantially affect cell viability and normal cell function, while hydrophobic insertion does not offer a permanent surface modification, with lipid–polymer conjugates rapidly dissociating from cells. [ 37,62,63 ] On the other end, introduction of bio‐orthogonal functionalities at the cell membrane offers clear advantages over nonspecific polymer conjugation, including better cytocompatibility and stability of conjugation. [ 64–66 ] The cell surface repertoire can be expanded to include abiotic functionality through the biosynthetic introduction of unnatural sugars into cellular glycans, a process termed metabolic oligosaccharide engineering (MOE).…”
Section: Covalent Conjugation Using Bio‐orthogonal Chemistrymentioning
confidence: 99%